Does Innovation Policy Matter in a Transition Country? The case of Hungary - Attila Havas (Hungarian Academy of Sciences, Institute of Economics, 2002)
The political and economic transition posed a complex, tremendous challenge in Hungary in the beginning of the 1990s. Not only macroeconomic stabilisation was required, but fundamental organisational and institutional changes were also needed to transform the country into a stable, middle-income economy, capable of catching up with the more advanced ones in the longer run. Having completed the first round of transition, Hungary has again reached a cross-roads. While the oneparty system has been replaced with a multi-party parliamentary democracy and the planned economy with a market economy based on private ownership, the world has significantly changed during this historically short period of time. Hungary now has to consider what role to play in the globalising learning economy, i.e. what future it envisions for herself. To be more specific, does the country passively accept the fate of a mere surviving economy, drifting without having its own strategy? Or, by implementing a clear strategy, does Hungary intend to be prosperous country, where in 15-20 years most citizens will enjoy high living standards, good health and a clean environment? The paper argues that a sound, coherent innovation policy is one of the cornerstones of an overall development strategy, required if a country is to excel. Yet, in spite of a number of efforts/ trials in the 1990s, no such policy document was approved in Hungary. The article first provides a brief overview of the transition process, emphasising the simultaneous need for systemic (institutional) changes and macroeconomic stabilisation in order to improve (micro)economic performance. Its core section analyses recent changes in the S&T decision- making system, various efforts to draft S&T and innovation policy documents, as well as the inputs and outputs of R&D and innovation. It concludes that the lack of an explicit innovation policy may hinder longterm development as such a policy is required to signal the main policy directions and commitments of the government, to strengthen the national inovation system thus anchor FDI and to align all public and private efforts, resources for development.
Keywords: 330